The story of Jesus in the world's literature - Wagenknecht, Edward, 1900-2004. (New York : Creative Age Press, 1946)
Includes selections from numerous authors.
His coming -- The hidden years -- Legends -- His work on earth -- The social gospel -- The passion drama -- Christ as redeemer and savior -- Afterwards -- Christ universal.
Includes indexes.
Keywords: Jesus Christ -- In literature